Endorser Strategies in Efforts to Increase Audience Purchase Interest in Social Commerce: A Systematic Literature Review - Sari, Prasiani Purnama (The Indonesian Journal of Communication Studies, 2024)
Social media has evolved into an advertising platform due to the active engagement of audiences, brands, and endorsers, giving rise to the new term 'social commerce,' which refers to trade activities involving social interaction. This research aims to compile studies on endorsers in social commerce and analyze the strategies employed to enhance the purchasing interest of the audience. The study utilizes the Systematic Literature Review method and identifies 15 documents meeting the criteria following a limitation process. The gathered strategies to support endorser and brand activities include enhancing parasocial relationships, possessing distinct characteristics, increasing interactions, utilizing attributes, garnering high numbers of 'likes' and 'comments,' avoiding hashtag usage, and informing about preannouncement discounts. This systematic literature review can be revisited to ascertain if there have been changes or additions to endorser strategies in social commerce, given the rapid evolution of algorithms and trends, necessitating adjustments from endorsers, brands, and relevant stakeholders.